2015
DOI: 10.3109/01913123.2015.1088909
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ultraviolet C radiation on the ultrastructure of the liver cells of mole rats

Abstract: The aim of this study was to elucidate the ultrastructural changes in the liver cells of mole rats (Spalax leucodon) exposed to ultraviolet radiation (UVR). Thirteen mole rats used in this study were caught from nature. They were divided into four groups. The first group was separated as a control and was not given any radiation. The rest were exposed to ultraviolet C (UVC) radiation for 7, 14, and 21 days. The electron microscopic examinations revealed that significant ultrastructural changes occurred in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
2
2
0
1
Order By: Relevance
“…Moreover, the current results are in accordance with the previous report of Tekın and Türker [118], who observed significant ultrastructural alterations in the liver tissue, including a decrease in cytoplasmic organelles, dilatation in rER, damage to the nucleus membrane, and widened and vacuolated mitochondria in the cytoplasm after 7, 14, and 21 days of UVC irradiation. The present results showed that the presence of pyknotic nuclei of the hepatocytes, swelling and vacuolation of mitochondria, and dilatation of rER in the cytoplasm were the most observable alterations in the hepatocytes of UVC-irradiated rats.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the current results are in accordance with the previous report of Tekın and Türker [118], who observed significant ultrastructural alterations in the liver tissue, including a decrease in cytoplasmic organelles, dilatation in rER, damage to the nucleus membrane, and widened and vacuolated mitochondria in the cytoplasm after 7, 14, and 21 days of UVC irradiation. The present results showed that the presence of pyknotic nuclei of the hepatocytes, swelling and vacuolation of mitochondria, and dilatation of rER in the cytoplasm were the most observable alterations in the hepatocytes of UVC-irradiated rats.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results have previously been detected by several authors [19,29,30]. Tekın et al [31] exhibited significant ultrastructural changes in liver cells of rats exposed to ultraviolet radiation (UV R) for 7, 14, and 21 days. These changes included a decrement of cytoplasmic organelles, dilatation of the rough endoplasmic reticulum, impairment of the nuclear membrane, expanded and vacuolated cytoplasmic mitochondria .IR-induced tissue damage activates both local and systemic inflammation processes resulting in increased plaque cell turnover and oxidative stress [32].…”
Section: Discussionsupporting
confidence: 88%
“…For example, the DNA glycosylase NEIL2 (involved in base excision repair) and the Xeroderma pigmentosum-associated XPA (a damage-specific DNA binding protein involved in nucleotide excision repair) are about 56- and 59-fold higher transcribed in normoxic Spalax liver than in rat. Overexpression of XPA in human cells increased their resistance to ultraviolet radiation-induced DNA damage 44 , 45 . However, more transgenic animal models or cell cultures with overexpressed repair genes, mimicking the natural gene expression pattern of mole rats, will be necessary to prove a direct correlation between increased levels of DNA damage and repair proteins and the longevity phenotype.…”
Section: Discussionmentioning
confidence: 99%